The potential of Community Based Tourism (CBT) and business with social impact in Bonito/MS (Research, Society and Development, 2022)
The objective of this work is to analyze business models with social impact and Community Based Tourism (CBT) in the context of Bonito/MS. The study has exploratory, descriptive characteristics, with a qualitative approach. Two businesses were identified: Instituto Família Legal and Instituto Visão de Vida. For the research, interviews were used and the data were treated considering the content analysis. Instituto Família Legal has attributes that qualify it as an impact business with monetary distribution and Instituto Visão de Vida has characteristics of a business with social impact, considering its transformation process. Both businesses are linked to CBT and could be leveraged from the development of partnerships that encourage social tourism and generate value for the region and population. Bonito/MS is a world-renowned tourist spot and this fact contributes to local development. In this way, the research starts from the premise that businesses with social impact can be developed allied to CBT.